Lignin derived carbon coated NiS / TiO2 composite material as well as preparation method and application thereof

By using lignin-derived carbon to coat NiS/TiO2 composite materials in sodium ion batteries, the problems of low NiS conductivity and dissolution shuttle of sodium polysulfide are solved, high specific capacity and cycle stability are achieved, and cost and energy consumption are reduced. , provides an economical and efficient negative electrode material solution.

CN119252874AActive Publication Date: 2025-01-03GUANGDONG UNIV OF TECH +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411143860.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-01-03
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode material NiS has low conductivity, volume expansion during circulation and dissolution shuttle problems of sodium polysulfide, resulting in poor cycle stability and high preparation cost.

Method used

Using sodium lignin sulfonate as a carbon precursor, lignin-derived carbon-coated NiS/TiO2 composite materials are prepared by hydrothermal and calcined treatment, and the adsorption capacity of TiO2 is used to alleviate the dissolution and shuttle problems of sodium polysulfide, and improve specific capacity and cycle stability. sex.

Benefits of technology

It achieves high specific capacity and excellent cycle stability, reduces preparation costs and energy consumption, simplifies the process flow, and provides an economical and efficient solution for negative electrode materials for sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005001681080000011
    Figure HDA0005001681080000011
  • Figure HDA0005001681080000012
    Figure HDA0005001681080000012
Patent Text Reader

Abstract

The invention discloses a lignin-derived carbon coated NiS / TiO2 composite material as well as a preparation method and application thereof. According to the preparation method, sodium lignin sulfonate is adopted as a carbon precursor, meanwhile, a substance TiO2 which has a relatively strong adsorption effect on sodium polysulfide is introduced, the NiS / TiO2 / C composite material with high specific capacity and good cycling stability is prepared through a hydrothermal and calcination treatment method, the preparation process is simple, the cost is low, and the composite material can be used as a high-specific-energy and high-stability sodium ion battery negative electrode material and has a good application prospect. The method has important significance on development of sodium-ion battery negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of high-value utilization of lignin and negative electrode materials for sodium ion batteries, and specifically relates to a lignin-derived carbon-coated NiS / TiO 2 Composite material and preparation method and application thereof. Background Art

[0002] In recent years, under the guidance of my country's "dual carbon" goals, the new energy industry has developed rapidly in response to the requirements of the times, and it is urgent to develop sustainable clean energy. Among them, rechargeable batteries have developed rapidly due to their high energy density and fast response. Lithium-ion batteries are currently the most widely used and most mature power battery technology. They have been widely used in portable power sources such as mobile phones and toys, as well as power batteries such as electric vehicles. However, due to insufficient lithium resources and the low safety of such batteries, their further development has been hindered.

[0003] Compared with lithium-ion batteries, sodium-ion batteries, as an emerging energy storage device, have many advantages. Sodium resources are abundant and widely distributed, the price is very low, and they are in the same main group as lithium, with similar physical and chemical properties. Therefore, sodium-ion batteries have great development prospects and are a good supplement and substitute for lithium-ion batteries. The operating voltage of sodium-ion batteries is relatively low, the electrolyte is not easy to decompose under high voltage, and the battery has better safety and stability. However, Na + The insertion and extraction of larger ionic radius during the charge and discharge process inevitably causes structural deformation and slow kinetics, resulting in capacity decay and poor cycle stability. Therefore, finding suitable sodium ion battery anode materials with high sodium storage capacity and excellent cycle performance is a key issue that needs to be solved urgently.

[0004] Transition metal sulfides have high theoretical specific capacity and excellent electrochemical reversibility, making them ideal candidates for anode materials for efficient sodium storage. Among various metal sulfides, nickel sulfide (NiS) has a high theoretical capacity of 590 mAh / g, is relatively easy to synthesize, and has higher electrochemical activity and conductivity than nickel sulfide systems and other metal sulfides. However, NiS anode has similar disadvantages to other metal sulfides, such as low electronic conductivity and large volume change during charge and discharge, and the sodium polysulfide produced during the cycle dissolves in the electrolyte, causing the shuttling of sodium polysulfide, resulting in a series of problems such as poor cycle stability and battery undervoltage failure.

[0005] In response to the above problems, researchers have proposed many methods to improve the sodium storage performance of NiS. For the problems of poor conductivity and volume expansion, there are mainly two solutions: (1) Through the design of nanostructures, the construction of multi-shell hollow structures, core-shell structures, etc. can effectively alleviate the volume expansion of the cycle process. At the same time, smaller nanoparticles can accelerate ion transport and electron transfer. Fan et al. prepared hierarchical sea urchin-like multi-shell hollow NiS@NCNT microspheres through chemical vapor deposition (CVD) and subsequent sulfurization strategy. This unique multi-shell hollow structure greatly improves the cycle stability, but the rate performance of the material is not excellent. At 2A·g -1 The current density is only 282.1 mAh·g -1 The specific capacity of NiS@C / rGO is higher than that of NiS@C / rGO, and this unique structural design is usually more complex and difficult to control. (2) Composite with carbon materials can effectively improve the conductivity and alleviate the volume change during the cycle. Song et al. prepared a double-layer carbon-coated NiS@C / rGO composite material using a simple hydrothermal reaction, PDA coating process and subsequent heat treatment. The results showed that the carbon-coated NiS@C / rGO composite material has a good conductivity and good conductivity. The carbon-coated NiS@C / rGO composite material has a good conductivity and good volume change ... -1 After 500 cycles at a current density of 240.2 mAh g -1 The capacity is maintained. However, the overall capacity of the material is low and the rate performance is poor. At the same time, relatively expensive chemicals such as polydopamine and graphene oxide lead to increased material preparation costs, which is not conducive to actual production and application. Regarding the dissolution and shuttling of sodium polysulfide generated during the cycle, some researchers have proposed to introduce elements with larger electronegativity such as N and S to construct polar CS bonds and anchor the dissolved sodium polysulfide intermediates. However, since the overall adsorption effect is not very ideal, the shuttling of sodium polysulfide is still inevitable during the cycle, damaging the diaphragm and causing sodium metal corrosion, resulting in potential battery failure.

[0006] Therefore, how to design and prepare a NiS carbon composite material with excellent electrochemical performance to address the problems of low NiS conductivity, volume expansion during the cycle, and dissolution and shuttling of sodium polysulfide is of great significance to the development of negative electrode materials for sodium ion batteries. Summary of the invention

[0007] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a lignin-derived carbon-coated NiS / TiO 2 A method for preparing a composite material.

[0008] The present invention adopts sodium lignin sulfonate, an ideal carbon precursor, and introduces TiO2, a substance that has a strong adsorption effect on sodium polysulfide. 2 NiS / TiO with high specific capacity and good cycle stability was prepared by hydrothermal and calcination treatment. 2As a negative electrode material for sodium ion batteries, / C composite material has a simple preparation process and low cost, which is of great significance to the development of negative electrode materials for sodium ion batteries.

[0009] Another object of the present invention is to provide a lignin-derived carbon-coated NiS / TiO 2 Composite materials.

[0010] Another object of the present invention is to provide the above-mentioned lignin-derived carbon-coated NiS / TiO 2 Application of composite materials.

[0011] The purpose of the present invention is achieved through the following technical solutions:

[0012] A lignin-derived carbon-coated NiS / TiO 2 The method for preparing the composite material comprises the following steps:

[0013] Using water as solvent, nickel salt, sulfur source, carbon source, small molecule diol and nano-TiO 2 or TiO 2 The precursors are mixed evenly, subjected to hydrothermal reaction at 80-250°C in a reactor for 4-20h, washed, dried, and calcined under a protective gas atmosphere to obtain lignin-derived carbon-coated NiS / TiO 2 Composite materials.

[0014] Preferably, the lignin-derived carbon coated NiS / TiO 2 The method for preparing the composite material comprises the following steps:

[0015] (1) Dissolve nickel salt and sulfur source in water, add carbon source and disperse evenly, add small molecule diol and mix evenly, and finally add nano-TiO 2 or TiO 2 The precursors are mixed evenly to obtain a mixed reaction liquid;

[0016] (2) The mixed reaction solution is subjected to hydrothermal reaction at 80-250°C in a reactor for 4-20 hours, washed, and dried to obtain carbon-coated NiS / TiO 2 Composite material precursors;

[0017] (3) Carbon-coated NiS / TiO 2 The composite material precursor was calcined under a protective gas atmosphere to obtain carbon-coated NiS / TiO 2 Composite materials.

[0018] Preferably, the nickel salt is at least one of nickel chloride hexahydrate and nickel nitrate hexahydrate.

[0019] Preferably, the sulfur source is at least one of thiourea and sodium thiosulfate pentahydrate.

[0020] Preferably, the carbon source is at least one of alkali lignin, lignin sulfonate, ammonia-oxidized lignin and enzymatic lignin; more preferably, it is at least one of sodium lignin sulfonate and ammonia-oxidized lignin.

[0021] More preferably, the ammonia-oxidized lignin is prepared by the following method:

[0022] (10-30) g of alkali lignin, (250-350) mL of water, (10-30) g of a 20-40 wt% hydrogen peroxide solution and (5-15) g of a 15-35 wt% ammonia solution are mixed evenly, and then subjected to hydrothermal reaction in a hydrothermal kettle at (100-180) ° C for (8-15) h. After removing water, ammonia oxidized lignin is obtained.

[0023] Preferably, the small molecule diol is at least one of ethylene glycol, propylene glycol and butanediol.

[0024] Preferably, the nano-TiO 2 Anatase TiO with an average particle size of 30 to 200 nm 2 ; the TiO 2 The precursor is at least one of tetrabutyl titanate and titanium isopropoxide.

[0025] Preferably, the nickel salt, sulfur source, carbon source, small molecule diol and nano-TiO 2 The ratio is 0.9g:(1.0~4.0)g:(0.1~3.0)g:(10~40)mL:(0.3~2.0)g; more preferably 0.9g:2.5g:0.6g:(10~25)mL:(0.3~0.5)g.

[0026] Preferably, the nickel salt, sulfur source, carbon source, small molecule diol and TiO 2 The ratio of the precursors is 0.9 g: (1.0-4.0) g: (0.1-3.0) g: (10-40) mL: (1.0-3.0) g; more preferably 0.9 g: 2.5 g: 0.6 g: (10-25) mL: 1.5 g.

[0027] Preferably, the volume ratio of the small molecule diol to water is (1-4):(1-4); more preferably (1-2.5):2.5.

[0028] Preferably, the temperature of the hydrothermal reaction is 100-180°C, and the time is 8-15 hours. More preferably, the temperature of the hydrothermal reaction is 150°C, and the time is 12 hours.

[0029] Preferably, the washing refers to centrifugal washing with water and anhydrous ethanol.

[0030] Preferably, the protective gas is at least one of nitrogen and a rare gas, more preferably at least one of nitrogen, argon and helium.

[0031] Preferably, the calcination temperature is 300-900° C., and the time is 2-5 hours; more preferably, the calcination temperature is 500-700° C., and the time is 3-5 hours.

[0032] Preferably, the heating rate of the calcination is 1 to 10°C / min.

[0033] A lignin-derived carbon-coated NiS / TiO prepared by the above preparation method 2 Composite materials.

[0034] The above-mentioned lignin-derived carbon coated NiS / TiO 2 Application of composite materials.

[0035] Preferably, the lignin-derived carbon coated NiS / TiO 2 Application of composite materials in sodium-ion batteries.

[0036] This patent will be described in more detail below.

[0037] (1) Evenly mix 0.9 g of nickel salt with 10-40 mL of ultrapure water;

[0038] (2) adding 1.0 to 4.0 g of a sulfur source to the solution obtained in step (1) and stirring until the solution is evenly dispersed;

[0039] (3) adding 0.1 to 3.0 g of a carbon source to the solution obtained in step (2) and stirring to dissolve;

[0040] In this step, adding different amounts of carbon source can play the role of carbon layer coating material after calcination, and the added carbon source content needs to be further determined through experiments. If the amount of carbon source added is too little, the generated carbon layer is thin and cannot effectively alleviate the volume expansion caused by the cycle process; if the amount of carbon source added is too much, more gas and foaming will be released during the pyrolysis process, resulting in less contact between the carbon layer and the material, greatly reducing the coating effect, and too much carbon content will reduce the relative content of NiS, resulting in a decrease in the specific capacity of the prepared negative electrode material.

[0041] (4) adding 10-40 mL of a small molecule diol to the solution obtained in step (3); stirring and mixing evenly;

[0042] In this step, a large amount of water is used as a solvent, and the material prepared after hydrothermal treatment will have a certain agglomeration phenomenon and poor cyclic stability. However, adding an appropriate amount of small molecule diol can adjust the solution viscosity, which is conducive to the control of crystal nucleus diffusion growth and the preparation of uniformly dispersed nanoparticles. At the same time, it can also maintain the solubility of the carbon source in the solution, so that the lignin carbon source can more evenly wrap the nickel salt and sulfur source, thereby improving the lignin-derived carbon-coated NiS / TiO 2 uniformity and increase the long-cycle stability of electrode materials.

[0043] (5) Add 0.3-2.0 g of nano-TiO to the solution obtained in step (4) 2 or 1.0-3.0 g TiO 2 The precursor is stirred continuously until it is evenly dispersed, then transferred into a reaction kettle and reacted at 100-180°C for 8-15h;

[0044] In this step, nano-TiO 2 Or adding different amounts of TiO 2 TiO generated by hydrothermal reaction of the precursor 2 TiO 2 It can be effectively compounded in electrode materials to achieve the adsorption of sodium polysulfide, alleviate the dissolution and shuttle of sodium polysulfide, and improve the cycle stability of the battery. 2 or TiO 2 The amount of precursor is too small, and the TiO generated by the reaction 2 It is not enough to adsorb the sodium polysulfide produced during the cycle, resulting in poor stability and battery failure; but due to TiO 2 Low theoretical specific capacity. If too much nano-TiO is added 2 or TiO 2 Precursor, which will result in a smaller overall specific capacity of the battery.

[0045] (6) The material obtained in step (5) was washed by centrifugation 3 times with water and anhydrous ethanol, and dried to obtain NiS 2 / TiO 2 / LS;

[0046] In this step, the main purpose is to wash away the incompletely reacted lignin and excess sulfur source to improve the purity of the material.

[0047] (7) calcining the powder obtained in step (6) at 300-900° C. for 2-5 h under a protective atmosphere to obtain the sodium ion battery negative electrode NiS / TiO 2 / C composite material.

[0048] In this step, the calcination temperature is 300-900°C. Due to the inherent characteristics of nickel sulfide and the reducibility of lignin carbon source, if the temperature is too low, the lignin will not be completely carbonized, and nickel chloride will be difficult to convert into high-crystalline NiS, and NiS / TiO with high purity and crystallinity cannot be prepared. 2 / C composite negative electrode material; if the temperature is too high, it may cause material loss and increase energy consumption, which is not green and energy-saving and will significantly increase costs.

[0049] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0050] (1) The present invention uses industrial lignin as a carbon precursor, and the reducing gas generated during the calcination process converts NiS 2 Reduction to NiS, no need to add additional H 2 / Ar mixed gas as a reducing agent, reducing energy consumption and costs, with high safety, while achieving high-value utilization of industrial lignin;

[0051] (2) The present invention only uses a hydrothermal method and a calcination process to prepare NiS / TiO 2 / C sodium ion battery negative electrode material, and the calcination temperature is low, which greatly reduces energy consumption and cost. The preparation process is simple and easy to operate, with high controllability, low energy consumption and high production efficiency;

[0052] (3) The composite material prepared by the present invention is a uniformly dispersed nanoparticle with a carbon layer coated on the surface, which is conducive to the transmission of ions and electrons and can also prevent the escape of polysulfide to a certain extent;

[0053] (4) NiS / TiO of the present invention 2 In the TiO / C composite material, the coated carbon layer can also effectively alleviate the volume change of the electrode material during the charge and discharge process. 2 It can achieve strong adsorption of sodium polysulfide, prevent polysulfide from escaping into the electrolyte, and thus solve the problem of undervoltage failure caused by polysulfide penetrating the membrane. The obtained material has high specific capacity and good cycle stability at high current density, and is an ideal negative electrode material for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 1 is the XRD diagram of the composite material prepared in Example 1 after calcination at different temperatures.

[0055] Figure 2 The NiS / TiO prepared in Example 1 2 EDX spectrum of / C composite materials.

[0056] Figure 3 The NiS / TiO prepared in Example 4 2EDX spectrum of / C composite materials.

[0057] Figure 4 The NiS / TiO prepared in Example 1 2 / C composite material was assembled into a button cell at a current density of 0.1A·g -1 The first charge and discharge curve at .

[0058] Figure 5 The NiS / TiO prepared in Example 1 2 / C composite material assembled into button-type batteries at different current densities.

[0059] Figure 6 The NiS / TiO prepared in Example 1 2 / C composite material was assembled into a button cell at 10A·g -1 Cycling performance diagram at different current densities.

[0060] Figure 7 The NiS / TiO prepared in Example 2 2 / C composite material was assembled into a button cell at 10A·g -1 Cycling performance diagram at different current densities.

[0061] Figure 8 The NiS / TiO prepared in Example 4 2 / C composite material was assembled into a button cell at 10A·g -1 Cycling performance diagram at different current densities.

[0062] Fig. 9 The NiS / C composite material prepared in Example 1 was assembled into a button cell at 10A·g -1 Cycling performance diagram at different current densities.

[0063] Fig.10 The NiS / TiO prepared in Comparative Example 2 2 / C composite material was assembled into a button cell at 10A·g -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION

[0064] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0065] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0066] The nano-TiO 2The average particle size of anatase TiO is 100 nm. 2 , purchased from McLean, item number: T861555-500g.

[0067] The ammonia-oxidized lignin described in the embodiment of the present invention is prepared by the following method:

[0068] 20 g of alkali lignin (Al) was added to 160 mL of ultrapure water, and then 20 g of H 2 O 2 (30 wt%) and 10 g NH 3 ·H 2 O (25wt%), stirred evenly, and subjected to hydrothermal reaction at 120°C in a hydrothermal reactor for 12h;

[0069] Then, rotary evaporate it, first add ice and rotary evaporate it for 3 hours to remove bubbles, then rotary evaporate it at room temperature for 3 hours, then increase the temperature to 60℃ and rotary evaporate it for 5 hours to dry, put it into a vacuum drying oven to dry overnight, and grind it after drying.

[0070] Example 1

[0071] (1) Add 0.9 g of nickel chloride hexahydrate to 25 mL of ultrapure water;

[0072] (2) adding 2.5 g of sodium thiosulfate pentahydrate to the solution obtained in step (1) and stirring until the solution is evenly dispersed;

[0073] (3) adding 0.6 g of sodium lignin sulfonate to the solution obtained in step (2) and stirring to dissolve;

[0074] (4) Add 25 mL of ethylene glycol to the solution obtained in step (3) and stir to mix evenly;

[0075] (5) Add 0.3 g of nano-TiO to the solution obtained in step (4) 2 , continue stirring until evenly dispersed, then transfer into the reactor and react at 150°C for 12h;

[0076] (6) washing the substance obtained in step (5) by centrifugation with water and anhydrous ethanol three times each, and drying for later use;

[0077] (7) The powder obtained in step (6) was heated to 600° C. at a heating rate of 5° C. / min and calcined for 4 h under a nitrogen atmosphere to obtain the sodium ion battery negative electrode NiS / TiO 2 / C composite material.

[0078] Repeat steps (1)-(6), except that the calcination temperature in step (7) was changed to 500°C and 700°C, to investigate the effect of different calcination temperatures on the NiS / TiO 2 / C composite materials.

[0079] Example 2

[0080] (1) Add 0.9 g of nickel chloride hexahydrate to 25 mL of ultrapure water;

[0081] (2) adding 2.5 g of sodium thiosulfate pentahydrate to the solution obtained in step (1) and stirring until the solution is evenly dispersed;

[0082] (3) adding 0.6 g of sodium lignin sulfonate to the solution obtained in step (2) and stirring to dissolve;

[0083] (4) Add 25 mL of ethylene glycol to the solution obtained in step (3) and stir to mix evenly;

[0084] (5) Add 0.5 g of nano-TiO to the solution obtained in step (4) 2 , continue stirring until evenly dispersed, then transfer into the reactor and react at 150°C for 12h;

[0085] (6) washing the substance obtained in step (5) by centrifugation with water and anhydrous ethanol three times each, and drying for later use;

[0086] (7) The powder obtained in step (6) was heated to 600° C. at a heating rate of 5° C. / min and calcined for 4 h under a nitrogen atmosphere to obtain the sodium ion battery negative electrode NiS / TiO 2 / C composite material.

[0087] Example 3

[0088] (1) Add 0.9 g of nickel chloride hexahydrate to 25 mL of ultrapure water;

[0089] (2) adding 2.5 g of sodium thiosulfate pentahydrate to the solution obtained in step (1) and stirring until the solution is evenly dispersed;

[0090] (3) adding 0.6 g of sodium lignin sulfonate to the solution obtained in step (2) and stirring to dissolve;

[0091] (4) Add 25 mL of ethylene glycol to the solution obtained in step (3) and stir to mix evenly;

[0092] (5) Add 1.5 g of titanium isopropoxide to the solution obtained in step (4), continue stirring until uniformly dispersed, then transfer to a reaction kettle and react at 150° C. for 12 h;

[0093] (6) washing the substance obtained in step (5) by centrifugation with water and anhydrous ethanol three times each, and drying for later use;

[0094] (7) The powder obtained in step (6) was heated to 600° C. at a heating rate of 5° C. / min and calcined for 4 h under a nitrogen atmosphere to obtain the sodium ion battery negative electrode NiS / TiO 2 / C composite material.

[0095] Example 4

[0096] (1) Add 0.9 g of nickel chloride hexahydrate to 25 mL of ultrapure water;

[0097] (2) adding 2.5 g of sodium thiosulfate pentahydrate to the solution obtained in step (1) and stirring until the solution is evenly dispersed;

[0098] (3) adding 0.6 g of sodium lignin sulfonate to the solution obtained in step (2) and stirring to dissolve;

[0099] (4) Add 25 mL of ethylene glycol to the solution obtained in step (3) and stir to mix evenly;

[0100] (5) Add 1.5 g of tetrabutyl titanate (TBOT) to the solution obtained in step (4), continue stirring until the solution is evenly dispersed, and then transfer the mixture into a reaction kettle and react at 150° C. for 12 h;

[0101] (6) washing the substance obtained in step (5) by centrifugation with water and anhydrous ethanol three times each, and drying for later use;

[0102] (7) The powder obtained in step (6) was heated to 600° C. at a heating rate of 5° C. / min and calcined for 4 h under a nitrogen atmosphere to obtain the sodium ion battery negative electrode NiS / TiO 2 / C composite material.

[0103] Example 5

[0104] (1) Add 0.9 g of nickel chloride hexahydrate to 25 mL of ultrapure water;

[0105] (2) adding 2.5 g of sodium thiosulfate pentahydrate to the solution obtained in step (1) and stirring until the solution is evenly dispersed;

[0106] (3) adding 0.6 g of ammonia-oxidized lignin to the solution obtained in step (2) and stirring to dissolve;

[0107] (4) Add 25 mL of ethylene glycol to the solution obtained in step (3) and stir to mix evenly;

[0108] (5) Add 0.3 g of nano-TiO to the solution obtained in step (4) 2 , continue stirring until evenly dispersed, then transfer into the reactor and react at 150°C for 12h;

[0109] (6) washing the substance obtained in step (5) by centrifugation with water and anhydrous ethanol three times each, and drying for later use;

[0110] (7) The powder obtained in step (6) was heated to 600° C. at a heating rate of 5° C. / min and calcined for 4 h under a nitrogen atmosphere to obtain the sodium ion battery negative electrode NiS / TiO 2 / C composite material.

[0111] Example 6

[0112] (1) Add 0.9 g of nickel chloride hexahydrate to 40 mL of ultrapure water;

[0113] (2) adding 2.5 g of sodium thiosulfate pentahydrate to the solution obtained in step (1) and stirring until the solution is evenly dispersed;

[0114] (3) adding 0.6 g of sodium lignin sulfonate to the solution obtained in step (2) and stirring to dissolve;

[0115] (4) Add 10 mL of ethylene glycol to the solution obtained in step (3) and stir to mix evenly;

[0116] (5) Add 0.3 g of nano-TiO to the solution obtained in step (4) 2 , continue stirring until evenly dispersed, then transfer into the reactor and react at 150°C for 12h;

[0117] (6) washing the substance obtained in step (5) by centrifugation with water and anhydrous ethanol three times each, and drying for later use;

[0118] (7) The powder obtained in step (6) was heated to 600° C. at a heating rate of 5° C. / min and calcined for 4 h under a nitrogen atmosphere to obtain the sodium ion battery negative electrode NiS / TiO 2 / C composite material.

[0119] Example 7

[0120] (1) Add 0.9 g of nickel chloride hexahydrate to 25 mL of ultrapure water;

[0121] (2) adding 1.0 g of sodium thiosulfate pentahydrate to the solution obtained in step (1), and stirring until the solution is uniformly dispersed;

[0122] (3) adding 0.6 g of sodium lignin sulfonate to the solution obtained in step (2) and stirring to dissolve;

[0123] (4) Add 25 mL of ethylene glycol to the solution obtained in step (3) and stir to mix evenly;

[0124] (5) Add 0.3 g of nano-TiO to the solution obtained in step (4) 2 , continue stirring until evenly dispersed, then transfer into the reactor and react at 150°C for 12h;

[0125] (6) washing the substance obtained in step (5) by centrifugation with water and anhydrous ethanol three times each, and drying for later use;

[0126] (7) The powder obtained in step (6) was heated to 600° C. at a heating rate of 5° C. / min and calcined for 4 h under a nitrogen atmosphere to obtain the sodium ion battery negative electrode NiS / TiO 2 / C composite material.

[0127] Example 8

[0128] (1) Add 0.9 g of nickel chloride hexahydrate to 25 mL of ultrapure water;

[0129] (2) adding 4.0 g of sodium thiosulfate pentahydrate to the solution obtained in step (1) and stirring until the solution is uniformly dispersed;

[0130] (3) adding 0.6 g of sodium lignin sulfonate to the solution obtained in step (2) and stirring to dissolve;

[0131] (4) Add 25 mL of ethylene glycol to the solution obtained in step (3) and stir to mix evenly;

[0132] (5) Add 0.3 g of nano-TiO to the solution obtained in step (4) 2 , continue stirring until evenly dispersed, then transfer into the reactor and react at 150°C for 12h;

[0133] (6) washing the substance obtained in step (5) by centrifugation with water and anhydrous ethanol three times each, and drying for later use;

[0134] (7) The powder obtained in step (6) was heated to 600° C. at a heating rate of 5° C. / min and calcined for 4 h under a nitrogen atmosphere to obtain the sodium ion battery negative electrode NiS / TiO 2 / C composite material.

[0135] Comparative Example 1

[0136] (1) Add 0.9 g of nickel chloride hexahydrate to 25 mL of ultrapure water;

[0137] (2) adding 2.5 g of sodium thiosulfate pentahydrate to the solution obtained in step (1) and stirring until the solution is evenly dispersed;

[0138] (3) adding 0.6 g of sodium lignin sulfonate to the solution obtained in step (2) and stirring to dissolve;

[0139] (4) Add 25 mL of ethylene glycol to the solution obtained in step (3), stir and mix evenly, then transfer to a reaction kettle and react at 150° C. for 12 h;

[0140] (5) washing the substance obtained in step (4) by centrifugation with water and anhydrous ethanol three times each, and drying for later use;

[0141] (6) The powder obtained in step (5) is heated to 600° C. at a heating rate of 5° C. / min under a nitrogen protective atmosphere and calcined for 4 h to obtain the sodium ion battery negative electrode NiS / C composite material.

[0142] Comparative Example 2

[0143] (1) Add 0.9 g of nickel chloride hexahydrate to 25 mL of ultrapure water;

[0144] (2) adding 2.5 g of sodium thiosulfate pentahydrate to the solution obtained in step (1) and stirring until the solution is evenly dispersed;

[0145] (3) adding 0.6 g of sodium lignin sulfonate to the solution obtained in step (2) and stirring to dissolve;

[0146] (4) Add 25 mL of ethylene glycol to the solution obtained in step (3) and stir to mix evenly;

[0147] (5) Add 0.2 g of nano-TiO to the solution obtained in step (4) 2 , continue stirring until evenly dispersed, then transfer into the reactor and react at 150°C for 12h;

[0148] (6) washing the substance obtained in step (5) by centrifugation with water and anhydrous ethanol three times each, and drying for later use;

[0149] (7) The powder obtained in step (6) was heated to 600° C. at a heating rate of 5° C. / min and calcined for 4 h under a nitrogen atmosphere to obtain the sodium ion battery negative electrode NiS / TiO 2 / C composite material.

[0150] Comparative Example 3

[0151] (1) Add 0.9 g of nickel chloride hexahydrate to 25 mL of ultrapure water;

[0152] (2) adding 2.5 g of sodium thiosulfate pentahydrate to the solution obtained in step (1) and stirring until the solution is evenly dispersed;

[0153] (3) adding 0.6 g of sodium lignin sulfonate to the solution obtained in step (2) and stirring to dissolve;

[0154] (4) Add 25 mL of ethylene glycol to the solution obtained in step (3), stir and mix evenly, then transfer to a reaction kettle and react at 150° C. for 12 h;

[0155] (5) washing the substance obtained in step (4) by centrifugation with water and anhydrous ethanol three times each, and drying the obtained powder for later use;

[0156] (6) Add 0.3 g of nano-TiO to the powder obtained in step (5) 2 , grind and mix evenly;

[0157] (7) The powder obtained in step (6) was heated to 600° C. at a heating rate of 5° C. / min and calcined for 4 h under a nitrogen atmosphere to obtain the sodium ion battery negative electrode NiS / TiO 2 / C composite material.

[0158] The morphology and size of the samples of the present invention were tested by field emission scanning electron microscopy (SEM, Hitach SU8220). The battery assembly was half-cell assembly, model CR2032. The negative electrode material was composed of 70wt% active material, 15wt% carbon black, and 15wt% carboxymethyl cellulose (CMC), wherein the active material was the NiS / TiO prepared in the above examples and comparative examples. 2 / C or NiS / C composite material. Sodium sheet was used as counter electrode, and the electrolyte was 1 mol / L NaPF 6 The sodium ion half-cell was prepared by using ethylene glycol dimethyl ether (DME) as the solvent and 1,2-dimethoxy- ... -1 and 10A·g -1 The constant current charge / discharge performance test of the battery was carried out at a current density of 0.5A·g -1 , 1A·g -1 , 2A·g -1 , 5A g -1 , 10A·g -1 , 20A·g -1 , 30Ag -1 The long cycle stability test was completed at 10A·g -1 At high current density.

[0159] Table 1 shows the NiS / TiO prepared in the examples. 2 / C composite electrode material and the sample prepared in comparative example at 10A·g -1 Comparison table of cycling performance under high current density.

[0160] Table 1

[0161]

[0162] Table 1 shows: NiS / TiO prepared in Example 1 2 / C negative electrode material at 10A·g -1At the current density, the initial capacity is 483.88 mAh / g, and after 1000 cycles, there is still a capacity retention rate of 82.41%, and there is no battery undervoltage failure problem, which is mainly attributed to the TiO 2 The adsorption of sodium polysulfide effectively prevents its dissolution and shuttling, achieves good cycle stability, and is significantly better than similar materials. In Example 2, 0.5 g of nano-TiO 2 It can achieve good cycle stability, but the capacity is relatively low. The materials prepared by using titanium isopropoxide and tetrabutyl titanate as titanium sources in Example 3 and Example 4, respectively, also have excellent cycle performance. Example 5 shows that the stability of the prepared material is also relatively excellent when ammonia-oxidized lignin is used as a carbon source. In Example 6, a small amount of ethylene glycol is used, and the prepared material shows a certain agglomeration phenomenon. Compared with Example 1, the capacity retention rate after 1000 cycles is lower. In Comparative Example 1, nano-TiO 2 , the charge-discharge mismatch began to appear at 350 cycles, and then the battery failed due to undervoltage, indicating that pure lignin carbon cannot effectively alleviate the sodium polysulfide shuttle effect. 2 Although the initial capacity is higher than that of Example 1, the cycle stability is poor, and the battery undervoltage failure problem occurs at 575 cycles. 2 , which may result in the TiO 2 Uneven distribution, less amount of TiO 2 It is not enough to adsorb the generated polysulfides and under-voltage failure problem will still occur.

[0163] Figure 1 The XRD patterns of the composite material in Example 1 of the present invention after calcination at different temperatures are shown in the figure. As can be seen from the figure, at above 600°C, along with the pyrolysis of lignin, NiS 2 It was successfully reduced by the pyrolysis products of lignin, and 600℃ was a dividing point for obtaining NiS materials with high purity and good crystallinity.

[0164] Figure 2 The NiS / TiO prepared in Example 1 2 The EDX spectrum of the NiS / TiO / C composite material shows that the material is evenly distributed. 2 The composite material is uniformly covered by an outer carbon layer.

[0165] Figure 3 The NiS / TiO prepared in Example 4 2 From the EDX spectrum of the / C composite material, it can be seen that the material is evenly distributed, but the particle size is relatively large, and some areas are not covered by the outer carbon layer.

[0166] Figure 4The composite material in Example 1 is -1 From the first charge and discharge curve at , we can see that the material has a high initial capacity and first coulombic efficiency.

[0167] Figure 5 The composite material NiS / TiO in Example 1 2 / C rate performance diagram at different current densities. It can be seen that the high specific capacity is still maintained at a high current density. When returning to a low current, the capacity is not significantly reduced compared with the initial capacity, indicating that the composite material has good reversibility.

[0168] Figure 6 The NiS / TiO prepared in Example 1 2 The button cell assembled with the / C composite material has a high current density of 10A·g -1 The long cycle performance diagram shows that adding an appropriate amount of nano-TiO 2 , which can effectively alleviate the dissolution and shuttling of sodium polysulfide and achieve excellent cyclic stability.

[0169] Figure 7 In Example 2, more nano-TiO 2 It can be seen that the prepared material also has excellent stability, but due to the TiO 2 If too much is added, the overall capacity will be reduced.

[0170] Figure 8 Example 4 uses tetrabutyl titanate as TiO 2 NiS / TiO prepared by precursor 2 / C composites at 10A·g -1 Cyclic performance diagram under current density, the material also has good cycle stability, but it may be due to the TiO prepared by tetrabutyl titanate 2 The purity is not high and the particle size is large, so more tetrabutyl titanate needs to be added, so the capacity will be reduced accordingly.

[0171] Fig. 9 The NiS / C composites with different lignin contents prepared in Comparative Example 1 were prepared at 10A·g -1 The cycling performance diagram under current density shows that the physical adsorption of lignin carbon alone is not enough to alleviate the dissolution and shuttling of polysulfides, which will cause potential battery undervoltage failure problems.

[0172] Fig.10 The NiS / TiO prepared in Comparative Example 2 2 / C composites at 10A·g -1 The cycle performance diagram under current density shows that the addition of nano-TiO 2It has a certain adsorption effect on polysulfides and improves the cycle stability to a certain extent, but due to the small amount used, there is still the problem of under-voltage failure.

[0173] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon-coated NiS / TiO2 composite material, characterized in that: The following steps are involved: Using water as solvent, nickel salt, sulfur source, carbon source, small molecule diol and nano-TiO2 or TiO2 precursor are evenly mixed, hydrothermally reacted at 80-250°C in a reactor for 4-20h, washed, dried and calcined under a protective gas atmosphere to obtain a lignin-derived carbon-coated NiS / TiO2 composite material.

2. The method for preparing a carbon-coated NiS / TiO2 composite material according to claim 1, characterized in that: The following steps are involved: (1) dissolving nickel salt and sulfur source in water, adding carbon source and dispersing them evenly, adding small molecule diol and mixing them evenly, and finally adding nano-TiO2 or TiO2 precursor and mixing them evenly to obtain a mixed reaction liquid; (2) hydrothermally reacting the mixed reaction liquid in a reactor at 80-250° C. for 4-20 hours, washing, and drying to obtain a carbon-coated NiS / TiO2 composite material precursor; (3) The carbon-coated NiS / TiO2 composite material precursor is calcined under a protective gas atmosphere to obtain a carbon-coated NiS / TiO2 composite material.

3. The method for preparing a carbon-coated NiS / TiO2 composite material according to claim 1, characterized in that: The ratio of the nickel salt, sulfur source, carbon source, small molecule diol and nano-TiO2 is 0.9g: (1.0-4.0)g: (0.1-3.0)g: (10-40)mL: (0.3-2.0)g; The ratio of the nickel salt, sulfur source, carbon source, small molecule diol and TiO2 precursor is 0.9g: (1.0-4.0)g: (0.1-3.0)g: (10-40)mL: (1.0-3.0)g; The volume ratio of the small molecule diol to water is (1-4): (1-4).

4. The method for preparing a carbon-coated NiS / TiO2 composite material according to claim 1, characterized in that: The nano-TiO2 is anatase TiO2 with an average particle size of 30 to 200 nm; The TiO2 precursor is at least one of tetrabutyl titanate and titanium isopropoxide; The carbon source is at least one of alkali lignin, lignin sulfonate, ammonia oxidized lignin and enzymatic lignin; The ammonia-oxidized lignin is prepared by the following method: 10-30g of alkali lignin, 250-350mL of water, 10-30g of a 20-40wt% hydrogen peroxide solution and 5-15g of a 15-35wt% ammonia solution are mixed evenly, and then subjected to hydrothermal reaction in a hydrothermal kettle at 100-180°C for 8-15h, and after removing water, the ammonia-oxidized lignin is obtained; The small molecule diol is at least one of ethylene glycol, propylene glycol and butanediol; The nickel salt is at least one of nickel chloride hexahydrate and nickel nitrate hexahydrate; The sulfur source is at least one of thiourea and sodium thiosulfate pentahydrate.

5. The method for preparing a carbon-coated NiS / TiO2 composite material according to claim 1, characterized in that: The calcination temperature is 300-900° C. and the calcination time is 2-5 hours; the protective gas is at least one of nitrogen and rare gas.

6. The method for preparing a carbon-coated NiS / TiO2 composite material according to claim 3, characterized in that: The ratio of the nickel salt, sulfur source, carbon source, small molecule diol and nano-TiO2 is 0.9g:2.5g:0.6g:(10-25)mL:(0.3-0.5)g; The ratio of the nickel salt, sulfur source, carbon source, small molecule diol and TiO2 precursor is 0.9g:2.5g:0.6g:(10-25)mL:1.5g; The volume ratio of the small molecule diol to water is (1-2.5):2.

5.

7. The method for preparing a carbon-coated NiS / TiO2 composite material according to claim 4, characterized in that: The carbon source is at least one of sodium lignin sulfonate and ammonia oxidized lignin.

8. The method for preparing a carbon-coated NiS / TiO2 composite material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 100-180°C and the time is 8-15h; The calcination temperature is 500-700°C and the calcination time is 3-5h; The heating rate of the calcination is 1-10°C / min.

9. A carbon-coated NiS / TiO2 composite material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the carbon-coated NiS / TiO2 composite material according to claim 9 in a battery.

Citation Information

Patent Citations

  • Preparation method of S / TiO2 composite material for anode of sodium-sulfur battery

    CN103840143A

  • Method for synthesizing TiO2 / C (titanium dioxide / carbon) composite material on basis of MOF (metal organic framework) structure and application

    CN107123803A

  • Preparation method of porous-structure sulfur electrode material

    CN107768659A

  • Lithium / sodium ion battery negative electrode material and preparation method thereof

    CN112599770A

  • Novel biomass carbon coated dual-phase Li4Ti5O12-TiO2 negative electrode material of lithium ion battery and application of biomass carbon coated dual-phase Li4Ti5O12-TiO2 negative electrode material

    CN112736236A